THE FORMATION OF READING LITERACY OF ELEMENTARY CLASS STUDENTS IN ENGLISH LANGUAGE TEACHING - Sadriddinova Guzaloy Erkin qizi (Bright Mind Publishing, 2025)
This article discusses the issues of forming students' reading literacy, developing text comprehension skills, increasing linguistic competencies, and strengthening communication skills in a foreign language through modern approaches and innovative methods in teaching English in primary grades. It also discusses the factors affecting their fluency in speech, the formation of quick and correct response skills, increasing their interest in knowledge, and thorough preparation for lessons. It also provides recommendations for increasing the effectiveness of learning through interactive and game methods.
Keywords: modern education, innovation, primary education, game methods, educational technologies, interactive methods.